Reading in English for Academic Purposes: A Case for Language Proficiency - Tan, Soon Hock (Journal of Modern Languages, 2017)
This study considers the issue of the relative importance of familiarity of content and language proficiency in reading in a second/foreign language. It also attempts to investigate the validity of the finding that language proficiency can short-circuit comprehension of a text written in that language for an academic purpose.